Key Articles and Guidelines in the Acute Management and Secondary Prevention of Ischemic Stroke. Issue 6 (11th February 2013) - Baker, William L.; Marrs, Joel C.; Davis, Lindsay E.; Nutescu, Edith A.; Rowe, A. Shaun; Ryan, Melody; Splinter, Michele Y.; Vardeny, Orly; Fagan, Susan C.
Abstract : Ischemic stroke is a prevalent disease with a large burden on the health system. It is essential for practitioners caring for patients who have experienced an ischemic stroke to be familiar with the literature supporting both acute management as well as secondary preventive strategies. Due to the large amount of literature available on this topic, this bibliography (the second of a two‐part series) aims to provide a comprehensive resource for medical practitioners charged with caring for this population. Acute management strategies involve controlling patients' blood pressure and administering thrombolysis (either pharmacologic or mechanical) to improve blood flow and preserve neurologic function. Various neuroprevention strategies have also been investigated. Secondary prevention strategies, similar to primary prevention, focus on modulation of various risk factors including antiplatelet treatments and control of blood pressure, and lipid levels, amongst others.